Gender-sensitive emergency responses with potato and sweetpotato, Ethiopia. Rebuilding food security after drought. Project profile. - International Potato Center (International Potato Center, 2019)
Potato and sweetpotato are ideal food security crops, producing good harvests even under challenging growing conditions. This project directly provided around 20,000 Ethiopian farm households in the Southern Nations, Nationalities and People’s (SNNP) region with quality planting materials and training, enabling them to rebuild their food security following a period of severe drought. Phase II will extend benefits to an additional 20,000 families in need of emergency support in SNNP and Amhara regions.